2013
DOI: 10.13005/ojc/290143
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Biocidal Study of Co(II), Cu(II) and Ni(II) Chelates of Nitrogen and Sulphur Containing Schiff Base Derived from 6-methyl-2-phenyl-4H-chromen-4-one

Abstract: INTRODUCTIONSchiff bases have the ability to act as coordinating ligands and the polynuclear complexes derived from Schiff bases find variety of applications in analytical and biological systems [1][2][3][4][5][6][7][8][9][10][11][12] . Schiff base complexes of transition metals are of great interest and have extensively been studied over past few decades [13][14][15][16] ABSTRACTIn the present paper, a series of complex of the type [MLX 2 ] where M = Co(II), Ni(II) and Cu(II), L = 6-methyl-2-phenyl-4H-chrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The Bordeaux mixture [1]. (Copper sulphate and hydrated lime) was the first fungicide to be used on a large scale world-wide [2,3]. Recent studies conducted showed that the use of copper significantly reduced the numbers of bacteria, filamentous fungi and yeast on leaf and fruit surfaces [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Bordeaux mixture [1]. (Copper sulphate and hydrated lime) was the first fungicide to be used on a large scale world-wide [2,3]. Recent studies conducted showed that the use of copper significantly reduced the numbers of bacteria, filamentous fungi and yeast on leaf and fruit surfaces [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is endowed with multiple applications like antihistamine activity, pharmacological activities such as antifungal, antiinflammatory, antimicrobial, anticonvulsant, antitumor, anticancer etc. It shows increased potency upon complexation with copper soaps [1][2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%